TREATMENT OF SMALL PELVIS VARICOSIS IN WOMEN (LITERATURE REVIEW - I. V. Shulikovskaya (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Small pelvis varicosis is a disorder the frequency of which is not yet clear to modern medicine, but its existence is unquestionable. Many problems in women's lives are connected with this pathology, but lack of developed diagnostics and necessary information about the disease make the women of this category dissatisfied with the achieved results of treatment.